2015
DOI: 10.1080/15384101.2015.1040965
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc is targeted to the proteasome for degradation in a SUMOylation-dependent manner, regulated by PIAS1, SENP7 and RNF4

Abstract: y These authors equally contributed to this work.Keywords: c-Myc, PIAS1, proteasome, SUMO, RNF4, SENP7 c-Myc is the most frequently overexpressed oncogene in tumors, including breast cancer, colon cancer and lung cancer. Post-translational modifications comprising phosphorylation, acetylation and ubiquitylation regulate the activity of c-Myc. Recently, it was shown that c-Myc-driven tumors are strongly dependent on the SUMO pathway. Currently, the relevant SUMO target proteins in this pathway are unknown. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 56 publications
(73 reference statements)
5
75
1
Order By: Relevance
“…However, RNF4-dependent protein stabilization as well as its transcriptional and biological activities were not affected by targeting SAE2 and inhibition of SUMOylation. SUMOylation was also reported to target c-Myc for degradation, and to maintain a c-Myc signature in MDA-MB-231 cells overexpressing MycER (González-Prieto et al, 2015; Kessler et al, 2012). Thus, differences in c-Myc levels and the biological context might account for these distinct cellular responses.…”
Section: Discussionmentioning
confidence: 97%
“…However, RNF4-dependent protein stabilization as well as its transcriptional and biological activities were not affected by targeting SAE2 and inhibition of SUMOylation. SUMOylation was also reported to target c-Myc for degradation, and to maintain a c-Myc signature in MDA-MB-231 cells overexpressing MycER (González-Prieto et al, 2015; Kessler et al, 2012). Thus, differences in c-Myc levels and the biological context might account for these distinct cellular responses.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is currently unclear, how SUMOylation exactly promotes c-Myc-driven tumorigenesis. Knocking down SUMO ligase PIAS1 reduced the SUMOylation levels of c-Myc and led to increased expression of a cMyc driven reporter gene [73], however inhibiting SAE2 repressed genes normally induced by c-Myc [69]. Despite these mechanistic questions, the finding that c-Myc driven tumors are dependent on a functioning SUMOylation system open up exciting new therapeutic opportunities to block this key oncogene [74].…”
Section: Sumoylation-mediated Regulation Of Oncogenes and Tumor Supprmentioning
confidence: 99%
“…E) However, the presence of multiple SUMO moieties can promote ubiquitylation via SUMO targeted ubiquitin ligases (Stubl) as described as a potential mechanism for c-Myc. SUMOylation via PIAS1 promotes ubiquitylation via the Stubl RNF4 and subsequent proteasomal degradation, thereby reducing transcriptional activity [73]. liver Overexpression of SUMO1 [111] colon Overexpression of SUMO1 [112] lip Overexpression of SUMO1 [113] gastric Upregulation of SUMO1 pseudogene3 [114] SUMO activating enzyme SAE1/2 gastric Overexpression of SAE2 [115] lung Overexpression of SAE2 [116] breast Low expression of SAE1 and SAE2 correlates with better survival [69] SUMO conjugating enzyme UBC9 lung Overexpression of UBC9 [117] primary colon and primary prostate Overexpression of UBC9 [64] metastatic breast, prostate and lung Downregulation of UBC9 [64] breast High levels of UBC9 correlate with higher risk for cancer and poor response to chemotherapy [118,119] multiple myeloma Overexpression of UBC9 [120] ovaries Overexpression of UBC9 [63] brain Overexpression of UBC9 [121] SUMO ligases PIAS1, PIAS2, PIAS3, PIASγ…”
Section: Figure 2 Sumoylation Of Important Cell Cycle Regulatorsmentioning
confidence: 99%
“…These modifications led to the rapid degradation of c-Myc in a proteasome-dependent manner. The authors showed that mutagenesis of all SUMOylation sites which were identified by mass spectrometry did not lead to a reduced SUMOylation of c-Myc, suggesting that the attachment of SUMO to a lysine residue might be promiscuous within the protein (36). These results are compatible with the idea that SUMO and ubiquitin modifications might be arbitrary in proteins that are targeted for degradation and the exact location of the modification plays a subordinate role here.…”
Section: Sumo Is Involved In Proteostasis Via Crosstalk With Ubiquitinmentioning
confidence: 99%